2021
DOI: 10.1098/rsif.2021.0318
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular morphology, task specialization and bite mechanics in Pheidole ants (Hymenoptera: Formicidae)

Abstract: Ants show remarkable ecological and evolutionary success due to their social life history and division of labour among colony members. In some lineages, the worker force became subdivided into morphologically distinct individuals (i.e. minor versus major workers), allowing for the differential performance of particular roles in the colony. However, the functional and ecological significance of these morphological differences are not well understood. Here, we applied finite element analysis (FEA) to explore the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 69 publications
(103 reference statements)
0
34
0
Order By: Relevance
“…In all insects with chewing mouthparts, bite forces are generated by large muscles located in the head capsule, and transmitted to the cutting edge of the mandible via an apodeme and a mandibular joint [20,21]. Because this musculoskeletal bite system is of behavioural, ecological and evolutionary relevance and can be analysed with first principles, it has received increasing attention from biomechanists [22][23][24][25], evolutionary biologists [26][27][28][29][30], functional morphologists [24,[31][32][33][34][35][36][37][38] and (behavioural) ecologists alike [21,[39][40][41][42][43][44]. Concretely, for an isometric contraction at zero fibre stretch, the force exerted at any point of the mandible, F b , may be written as the product between the ratio of muscle volume V m and the average fibre length L f (the physiological cross-sectional area of the muscle, A phys = V m /L f ), the muscle stress σ m , the cosine of the average pennation angle w, and the mechanical advantage MA [21,31,39,41]:…”
Section: Introductionmentioning
confidence: 99%
“…In all insects with chewing mouthparts, bite forces are generated by large muscles located in the head capsule, and transmitted to the cutting edge of the mandible via an apodeme and a mandibular joint [20,21]. Because this musculoskeletal bite system is of behavioural, ecological and evolutionary relevance and can be analysed with first principles, it has received increasing attention from biomechanists [22][23][24][25], evolutionary biologists [26][27][28][29][30], functional morphologists [24,[31][32][33][34][35][36][37][38] and (behavioural) ecologists alike [21,[39][40][41][42][43][44]. Concretely, for an isometric contraction at zero fibre stretch, the force exerted at any point of the mandible, F b , may be written as the product between the ratio of muscle volume V m and the average fibre length L f (the physiological cross-sectional area of the muscle, A phys = V m /L f ), the muscle stress σ m , the cosine of the average pennation angle w, and the mechanical advantage MA [21,31,39,41]:…”
Section: Introductionmentioning
confidence: 99%
“…Unusual mandibular shapes have also been a special point of interest in Cretaceous ants, especially in the †Haidomyrmecinae (Barden et al 2020) and †Zigrasimeciinae (Cao et al 2020). The biomechanics of the long, saber-shaped mandibles of Harpegnathos have been studied in several publications (Zhang et al 2020a(Zhang et al , b, 2021, whereas no ant species with 'normal' mandibles has received similar attention, with the arguable exception of leaf cutting ants (Püffel et al 2021) and a single analysis of Pheidole mandibles (Klunk et al 2021).…”
Section: Evolution Of the Ant Mandiblementioning
confidence: 99%
“…Although recent attempts suggest that the morphological variation between Pheidole species in head shape and size seems not to be related to differences in diet (Casadei-Ferreira et al, 2021;Holley et al, 2016), little is known about how the head shape is associated with the mechanical demands of biting, which differ between worker subcastes. Recent works suggest that even slight morphological modifications in Pheidole worker mandibles could lead to differences in bite performance between worker subcastes and species, according to the primary roles of each worker subcaste in the colony (Huang, 2012;Klunk et al, 2021), as also observed in other ants (Larabee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%